Segmentación y Conteo de las Líneas de la Nariz del Feto en Imágenes Ecográficas de las 11-13+6 Semanas de Gestación - Ballesteros Maldonado, Angee Paola; López Alza, Laura Catalina; Herrera Garcia, Rodrigo Javier (Ingeniería, 2015)
This document introduces a method for nasal segmentation and the subsequent counting of lines corresponding to the skin, nasal bone and the tip of the nose in 2D fetal ultrasound images of the first gestational trimester from 11 to 13 weeks and 6 days (11-13+6 weeks). Presence of the three lines in the nasal region is one of the features that should have the fetus on ultrasound image to ensure the reliability of the measurement of fetal nuchal translucency thickness; this measurement is used to identify the possible existence of syndromes or chromosomal abnormalities. The method is applied to the mid-sagittal head plane where the hyperintense regions have been identified. The segmentation is hierarchical: first, the nose is identified by the combination of a regional maxima and high eccentricity detection algorithms; then the aforementioned lines are identified using K-means clustering and mathematical morphology. Because of uncertainty between images with respect to fetal position, resolution, noise and dynamic range, the results ranging from cases in which the region of interest is not found, to those where the lines are clearly identifiable.